Mental health and social support among Saudi antenatal clients during the COVID-19 crisis - Junel Bryan Bajet; Nahed Alquwez; Shiela Soriano; Jennifer Mesde; Ejercito Balay-Odao; Gabby Cacho; Jonas Cruz (Kashan University of Medical Sciences, 2023)
Background: A healthy mental state is essential throughout pregnancy. The Coronavirus disease 2019 (COVID-19) pandemic has posed a challenge to psychological resilience, especially among pregnant women.Objective: This study measured the mental health and social support of Saudi pregnant women during the COVID-19 pandemic.Methods: The study utilized a cross-sectional design, with 243 respondents as its convenience sample from hospitals and health centers in Al Duwadimi, Saudi Arabia. This study applied the "Arabic Version of the Depression, Anxiety, and Stress Scale" and the "Multidimensional Scale for Perceived Social Support for Arab Women." The Pearson correlation was used to measure the association between respondents' profiles and social support. Multiple regression analysis was used to measure predictors of mental health.Results: The pregnant women had normal depression levels, extremely severe anxiety, and severe stress. The pregnant women also perceived high social support. A very weak inverse association was found between age and number of children with overall social support. Social support, especially from the husband, decreased the depression level in the pregnant women.Conclusion: Pregnant women in Saudi Arabia experienced higher levels of depression, anxiety, and stress during the COVID-19 outbreak, which was linked to the support they received from their relatives. This finding implies the need to enhance support from family members during infectious disease outbreaks.